2019
DOI: 10.1097/md.0000000000016309
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the prognosis of papillary and clear cell renal cell carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…[6][7][8] However, conflicting results were observed in other studies, in which metastatic pRCC and metastatic ccRCC had similar prognoses. 9,10 In addition to the current contradictory evidence, few studies have focused on comprehensive subgroup analyses based on demographic and clinical factors. In the present study, our purpose was to evaluate the survival outcomes of pRCC and ccRCC using the Surveillance, Epidemiology, and End Results (SEER) database.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] However, conflicting results were observed in other studies, in which metastatic pRCC and metastatic ccRCC had similar prognoses. 9,10 In addition to the current contradictory evidence, few studies have focused on comprehensive subgroup analyses based on demographic and clinical factors. In the present study, our purpose was to evaluate the survival outcomes of pRCC and ccRCC using the Surveillance, Epidemiology, and End Results (SEER) database.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies concluded that the prognosis of localized pRCC was more favorable than that of ccRCC, while the prognosis of advanced/metastatic pRCC was worse than that of ccRCC 6‐8 . However, conflicting results were observed in other studies, in which metastatic pRCC and metastatic ccRCC had similar prognoses 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Exophytic renal tumors tended to be associated with lower pathologic grade and the presence of papillary renal cell carcinoma subtype when compared with endophytic renal tumors [ 25 ]. Papillary renal cell carcinoma is reported to have better outcomes than clear cell renal cell carcinoma in patients without metastases [ 26 ]. Furthermore, the presence of an angular interface with the normal renal parenchyma is strongly related to benignity in an exophytic renal mass.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of RCC has been increasing in the recent decades, which accounts for 3% of all adult malignancies and ranks the 13th most common malignancy diagnosed worldwide annually. RCC originates from renal epithelial cells (1), and nearly 70-80% cases of RCC is ccRCC pathologic subtype (2). Late diagnosis is a major obstacle to improving ccRCC outcomes, with the fact of about 33% of ccRCC patients initially diagnosed as advanced stage and 40% of those will eventually have distant metastasis.…”
Section: Introductionmentioning
confidence: 99%